The violation of Grice's Maxims in Gotcha Calls / Al-Shaatha Nasser Al-Kharusi - Al-Kharusi, Al-Shaatha Nasser (2012)
This study investigates prank calls in Gotcha Calls. It aims to find the framing of Gotcha Calls, how they are structured in relation to Grice’s maxim of quality and the victims’ reactions to the deceptive behavior in these calls. Second, it aims to find how politeness shifts at the different stages in the call: before the fabrication, during the fabrication and after the fabrication is shifted to reality. Third, the role of knowledge schemata in relation to identity and power distribution is examined. A content analysis, politeness relational work and Grice’s maxims were used to answer the three research questions. Twenty seven Gotcha Calls were downloaded from the Malaysian radio station web site Hitz Dot FM. Findings show that all calls followed the same structure and the violation of the maxim of quality played a major role in these calls. Second, even though the maxim of quality was violated most people accepted this deceptive behavior as acceptable behavior for the specific context (Gotcha Calls) in which it occurs. Third, the maxim of quality played a significant role in politeness where participants were found to shift their strategies from being polite before the violation of the maxim of quality to being impolite after the violation of the maxim of quality. Fourth, the knowledge schemata was found to play a role in these calls especially in constructing the call, the establishment of identities and power distribution during the interaction.